Social vulnerability and the impact of policy responses to COVID‐19 on disabled people - Mladenov, Teodor; Brennan, Ciara Siobhan (Sociology of Health & Illness, 2021)
In this paper, we propose a conceptual framework for understanding the impact of the policy responses to COVID-19 on disabled people. These responses have overwhelmingly focused on individual vulnerability, which has been used as a justification for removing or restricting rights. This suggests the need to shift the attention towards the social determinants of disabled people's vulnerability. We do this by bringing literature on social vulnerability in disaster risk management or 'disaster studies' in contact with key concepts in disability studies such as the social model of disability, independent living, intersectionality, and biopower. Empirically, we draw on the findings of the global COVID-19 Disability Rights Monitor (www.covid-drm.org), as well as on reports from academic journals, civil society publications, and internet blogs. We put the proposed conceptual framework to work by developing a critical analysis of COVID-19 policies in three interrelated areas-institutional treatment and confinement of disabled people, intersectional harms, and access to health care. Our conclusion links this analysis with strategies to address disabled people's social vulnerability in post-pandemic reconstruction efforts. We make a case for policies that address the social, economic, and environmental conditions that disproportionately expose disabled people to natural disasters and hazards.
Keywords: approches et analyses; capacitisme; corps; covid-19; discipline; intersectionnalité; ressource en ligne; santé; sciences humaines; sociologie; soins de santé; systèmes d'oppressions; thématiques; vulnérabilité

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Vote, ovocytes et cosmétiques. Les trois jalons identitaires du recours au genre dans la recherche sur les cellules souches en Californie - Thompson, Charis; Sofio, Séverine (Cahiers du Genre, 2014)
Cet article explore les trois jalons identitaires du recours au genre [punctuated gendering] dans la recherche biomédicale sur les cellules souches en Californie. J’y défends l’idée selon laquelle le développement de ce secteur a eu besoin des femmes à trois reprises, mais pas de toutes les femmes à chaque fois. En d’autres termes, suivant les étapes que franchissait le développement de l’innovation autour des cellules souches, les femmes ont été sollicitées en fonction d’une perception du genre à chaque fois différente. Ainsi, il a d’abord fallu faire appel à elles en tant que citoyennes, au croisement des rapports de sexe, de race et de classe ; on a ensuite eu besoin d’elles en tant que corps biologiques ; elles ont, enfin, été sollicitées en tant que consommatrices. Le but de ce triple recours aux femmes selon des identités de genre à chaque fois spécifiques, fut d’abord d’attirer des capitaux publics et privés dans ce secteur, une fois le soutien de l’état californien garanti ; puis d’assurer l’approvisionnement de la recherche en morceaux de corps humain ; et enfin, de permettre le développement de l’économie autour de l’innovation sur les cellules souches. Cet article s’appuie sur mes précédents travaux sur la biomédicalisation et la marchandisation de la reproduction, mais il s’inscrit également dans la perspective des théories de la division sexuée du travail, et de la construction sociale du genre par la publicité et la consommation. Au croisement de ces logiques, l’innovation biomédicale apparaît donc comme un espace privilégié pour étudier le genre comme répertoire identitaire dynamique, à travers une mise en œuvre concrète de l’idée d’intersectionnalité.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; intersectionnalité; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Vieillissement réussi : perception des femmes aînées immigrantes de l’Afrique noire à Montréal - Noubicier, Agnès Florette; Charpentier, Michèle (Santé mentale au Québec, 2013)
Le présent article s’intéresse aux femmes aînées des communautés ethnoculturelles de l’Afrique noire. Il a pour but de présenter le sens qu’elles donnent au « vieillissement réussi » dans leur pays d’accueil, et de mettre en évidence les facteurs qu’elles considèrent comme essentiels pour expérimenter « un maximum de satisfaction et de bonheur » au cours de cette étape de leur vie. Il s’appuie sur une étude qualitative exploratoire menée auprès de sept femmes âgées de 65 à 77 ans qui ont immigré au Québec alors qu’elles avaient plus de 50 ans. L’étude met en relief des femmes aux identités multiples et aux vieillissements différentiels, pour qui le « vieillissement réussi » est tributaire de leur implication dans la famille et dans la société, de la foi et de l’autonomie financière. L’analyse des résultats sous un angle intersectionnel permet aussi de noter que les femmes aînées immigrantes de l’Afrique noire connaissent des difficultés en raison de l’entrecroisement des effets dus à leur âge, leur appartenance ethnique et leur genre, avec d’autres aspects liés à leur identité tels que la culture, la langue, le sexe, le parcours migratoire. Une multitude d’obstacles jonchent alors leur processus de vieillissement et influent sur leur conception du « vieillissement réussi
Keywords: 2000 à aujourd'hui; accomplissement; afrique; afrique noire; amériques; approches et analyses; cours; discipline; femmes aînées; femmes immigrantes; intersectionnalité; périodes historiques; québec; récits de vie; régions géographiques; santé; santé mentale; sciences humaines; soc1061; sociologie; thématiques; travail social; vieillissement